EFFECT OF LAUGH THERAPY ON THE STRESS THE ELDERLY AT THE WERDHA BINA BHAKTI NURSING HOME IN 2020 - Royani; Ambiya Aulia; Tirta Yenti (Jurnal Kesehatan STIKes IMC Bintaro, 2020)
When a person enters old age, various changes occur that are physical, mental, and social. And one of the psychological problems that can be experienced by the elderly is stress. This type of therapy that can reduce stress is laughter therapy a way to help someone in dealing with problems, such as stress, anger, and saturation. The purpose of this study was to determine the effect of laughter therapy on stress the elderly in nursing bina bhakti in serpong. The research methodology in this study uses a quantitative approach to the type of research Quasy Experiment Design, One Group Pretest Posttes Design. Quota Sampling, sampling technique a sample of 32 elderly, the sample in this study were elderly aged 60-86. Statistical tests using the Paired Samples T-test. The results showed that before laughter therapy, 14 people (43.8) experienced mild stress, 17 people (53.1) experienced moderate stress. After laughter therapy, 15 people (46.9) become mild stressed, 10 people (31.3) become normal. Data analysis using Paired Samples T-test states that p (0,000) <a (0.05) thus Ho is rejected and Ha is accepted. The conclusion is that there is a significant difference between before and after doing there is the effect of laughter therapy on the stress in the elderly at the Werdha Bina Bhakti Nursing Home. Suggestions to improve gerontik nursing care so as to reduce stress in the elderly.